TODAY'S REQUIREMENTS FOR TEACHING MATHEMATICS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article describes the indicators that should be achieved in the implementation of the tasks set forth in the Concept for the development of mathematics in the system of public education of the Republic of Uzbekistan, and the necessary conditions for the development of mathematical literacy in the education system.